Describing the profile of a population of UK veterans seeking support for mental health difficulties. (2nd November 2019) - Murphy, Dominic; Ashwick, Rachel; Palmer, Emily; Busuttil, Walter
Abstract: Background : Evidence suggests that veterans with mental health issues have poorer treatment outcomes than civilian counterparts. Understanding the difficulties faced by veterans could help focus treatments and improve outcomes. Aims : To survey a representative sample of treatment-seeking veterans to explore their mental health needs. Methods : A random sample of UK veterans who had engaged with a national mental health charity in the UK was drawn. Individuals completed questionnaires about their health, military experiences and pre-enlistment vulnerabilities. Results : Four hundred and three out of six hundred (67.2%) participants returned completed questionnaires. PTSD was the most commonly endorsed mental health difficulty (82%), followed by problems with anger (74%), common mental health difficulties (72%) and alcohol misuse (43%). Comorbidity was frequent; with 32% of those with PTSD meeting criteria for three other health outcomes versus only 5% with PTSD alone. Conclusions : Results indicate the complexity of presentations within treatment seeking veterans. These difficulties may partly explain the poorer treatment outcomes reported in veterans in comparison to the general public. As such, it would be prudent for interventions targeted at veterans with mental health difficulties to attempt to address the range of issues faced by this population rather than focus on a particular presenting problem.